Solutions to Improve the Efficiency of Import Full Container Load Freight Forwarding Procedure by Sea at Glotrans Da Nang Branch - Pham, Tran Nhat Phuong (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Logistics and Digital Supply Chain Management; 2021-2025.